Pelatihan Strategi "Hook" Konten Video Sosial Media Phoenix Radio Bali untuk Meningkatkan Brand Awareness - Amanda, I Gusti Ayu Rachel; Pratiwi, Nuning Indah (Empowerment, 2024)
This article discusses the "HOOK" strategy in social media video content used by Phoenix Radio Bali to increase brand awareness. Phoenix Radio Bali utilizes social media to reach a wider audience, especially the younger generation. However, some of the videos that were previously made have not been effective in attracting the audience's attention. Therefore, the author provides this training with the aim of providing an understanding of the "HOOK" strategy in creating video content to increase the effectiveness of videos in attracting the audience's attention and increasing Phoenix Radio Bali's brand awareness. The implementation method with training takes place in several stages. Starting with analyzing the concept and importance of social media for radio in the digital era. The results of the service, namely education and training on the 'HOOK' strategy in social media video content, are important steps that must be taken by Phoenix Radio Bali. Inadequate understanding of the 'HOOK' concept among the content team has led to limitations in creating effective video content to attract attention and maintain audience engagement